2002
DOI: 10.1073/pnas.162097799
|View full text |Cite
|
Sign up to set email alerts
|

Roles of mutation and recombination in the evolution of protein thermodynamics

Abstract: We present a comprehensive study of the evolutionary origin of the thermodynamic behavior of proteins. With the use of a simplified model, we exhaustively enumerate the space of all sequences and the space of all structures, simulate the evolutionary relationship between sequences and structures, and characterize the steady-state sequence distribution for all structures in terms of several thermodynamic variables. We assess the effects of two major forces of evolution: mutation and recombination. Three simplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 58 publications
4
64
0
Order By: Relevance
“…This theoretical prediction is consistent with subsequent experiments on b-lactamase indicating that for a given number of amino acid substitutions, recombined variants are much more likely to retain function than variants generated by random point mutations [339]. In another simulation study, evolutionary dynamics that admits both point mutations and recombination leads to a much higher concentration of population in the prototype sequence than if evolution proceeds via point mutations alone, suggesting a significant role of recombination in the prototype-like behaviours of natural proteins [152].…”
Section: Predictions and Rationalizationssupporting
confidence: 81%
See 1 more Smart Citation
“…This theoretical prediction is consistent with subsequent experiments on b-lactamase indicating that for a given number of amino acid substitutions, recombined variants are much more likely to retain function than variants generated by random point mutations [339]. In another simulation study, evolutionary dynamics that admits both point mutations and recombination leads to a much higher concentration of population in the prototype sequence than if evolution proceeds via point mutations alone, suggesting a significant role of recombination in the prototype-like behaviours of natural proteins [152].…”
Section: Predictions and Rationalizationssupporting
confidence: 81%
“…These sequences are often also thermodynamically most stable [137]. But random mutations alone-in the absence of a fitness drive towards higher native stability-are not sufficient to produce a highly concentrated population at the most stable 'prototype' sequence at the bottom of the sequence-space superfunnel because of the large number of sequences that are less stable [40,137,152,153]. Therefore, the experimental observation that natural proteins are often a nearly most stable sequence that behaves like a prototype sequence suggests strongly that they are results of positive selection for higher native stability (see further discussion in §3.2.3).…”
Section: Reconciling Evolutionary Selection For Stability With Marginmentioning
confidence: 99%
“…The germ of this concept originated with Maynard-Smith 108 , and it was further developed by Schuster and collaborators 58 , who showed that the neutral networks associated with many individual minimum free energy RNA secondary structures are vast and span sequence space. Neutral networks were later characterized in proteins [109][110][111][112] , and the concept can even be applied to higher-order molecular systems, such as regulatory networks 47 . The biological importance of this concept is underscored by molecular evolution studies showing that very different RNA or protein molecules and their intermediates can have identical structure or function.…”
Section: Box 2: Neutral Networkmentioning
confidence: 99%
“…Xia and Levitt [80] used a 5 × 5 two-dimensional square lattice model of proteins to test for the effects of recombination and mutation in the evolution of protein thermodynamics. They explored all the sequences in the lattice assuming that the protein sequences that fold into the same structure and that differ by a single mutation constituted a neutral network.…”
Section: Revisiting Recombination From a Thermodynamic Point Of Viewmentioning
confidence: 99%